2018
DOI: 10.5539/enrr.v8n1p70
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Carbon and Nitrogen Stocks Following Land Use Changes in a Sub-Humid Climate

Abstract: There has been an incessant conversion of natural forests to agricultural land uses such as farmlands, grasslands and parkland agro-forestry in Africa during the last century. This study investigated changes in soil organic carbon (SOC) and total nitrogen (TN) stocks following the conversion of a natural forest to coffee-based agro-forestry, grazing grassland and well-managed maize farm in a sub-humid tropical climate of Ethiopia. Soil samples (up to 1m depth) were taken from each of these four land use types.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Tis was attributed to an increase in the mineralization rate and a decrease in the soil accumulation of soil organic carbon and total nitrogen stock; even though the results of a one-way ANOVA revealed an insignifcant diference in the carbon-to-nitrogen ratio, it was estimated to decline by 3.32% with natural forestland use types. Te higher correlation between soil organic carbon and total nitrogen stock showed that the main source of total nitrogen is the decomposition of organic matter [55,63]. In general, the soil C : N ratio is an essential indicator of the soil nutrient storage and recycling capacity, carbon storage, greenhouse gas emissions, and the microorganism community structure that changes the soil quality of ecosystems.…”
Section: Carbon-to-nitrogen Ratio and Correlation Of Carbon-mentioning
confidence: 99%
“…Tis was attributed to an increase in the mineralization rate and a decrease in the soil accumulation of soil organic carbon and total nitrogen stock; even though the results of a one-way ANOVA revealed an insignifcant diference in the carbon-to-nitrogen ratio, it was estimated to decline by 3.32% with natural forestland use types. Te higher correlation between soil organic carbon and total nitrogen stock showed that the main source of total nitrogen is the decomposition of organic matter [55,63]. In general, the soil C : N ratio is an essential indicator of the soil nutrient storage and recycling capacity, carbon storage, greenhouse gas emissions, and the microorganism community structure that changes the soil quality of ecosystems.…”
Section: Carbon-to-nitrogen Ratio and Correlation Of Carbon-mentioning
confidence: 99%